1986
DOI: 10.1161/01.hyp.8.5.372
|View full text |Cite
|
Sign up to set email alerts
|

Selective vasodilation produced by renal denervation in adult spontaneously hypertensive rats.

Abstract: The kidneys of adult male spontaneously hypertensive rats (SHR) were denervated, and systemic and regional blood flows were measured 3 to 5 hours or 5 days after denervation. Arterial pressure was reduced 20 to 27% in denervated SHR during both periods compared with that in sham-operated SHR (iliolumbar blood vessels painted with phenol). This hypotensive response was produced by a 32 to 35% reduction in total peripheral resistance. At 3 to 5 hours and at 5 days, a major decrease in total peripheral resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This hypotensive effect of ARN-x is small in comparison with the 20-27% reductions in arterial blood pressure after complete renal denervation in adult SHR. 9 In other reports, however, renal denervation failed to induce a hypotensive effect in SHR when hypertension was established. 8 Nevertheless, our data suggest that the reported hypotensive effects of total renal denervation in young as well as in adult SHR (see 13,14,33) are mainly due to the loss of the ERN.…”
Section: Figure 2 Bar Graphs Showing Baroreceptor Reflex Sensitivitymentioning
confidence: 93%
See 3 more Smart Citations
“…This hypotensive effect of ARN-x is small in comparison with the 20-27% reductions in arterial blood pressure after complete renal denervation in adult SHR. 9 In other reports, however, renal denervation failed to induce a hypotensive effect in SHR when hypertension was established. 8 Nevertheless, our data suggest that the reported hypotensive effects of total renal denervation in young as well as in adult SHR (see 13,14,33) are mainly due to the loss of the ERN.…”
Section: Figure 2 Bar Graphs Showing Baroreceptor Reflex Sensitivitymentioning
confidence: 93%
“…To assess the contribution of the sympathetic nervous system tone to the maintenance of blood pressure in these conscious animals, changes in mean arterial pressure and heart rate were recorded (mean of 5-15 minutes) after intravenous injection of 20 mg/kg hexamethonium (Sigma Chemical Co.), which causes total ganglionic blockade in rats. 9 Plasma and tissue norepinephrine determination. Before any drugs were given (day 1) a 0.5 ml arterial blood sample was taken from all rats for determination of plasma norepinephrine levels.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many of the early studies reported that renal denervation slowed or delayed the rise in blood pressure in experimental models of hypertension such as spontaneous hypertension [70][71][72], Dahl hypertension [73 && ], N v -nitro-L-arginine methyl ester (L-NAME) induced hypertension [74], angiotensin II induced hypertension and deoxycorticosterone acetate (DOCA)-salt hypertension [75,76]. This regulatory modulation of blood pressure by the renal sympathetic nerves is further evidenced by the higher sympathetic nerve activity in patients with renal failure conditions [77,78].…”
Section: Sympathetic Nervous System and Blood Pressure Controlmentioning
confidence: 99%